2007
DOI: 10.1108/01439910710749609
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of current trends in shape memory alloy actuators for intelligent robots

Abstract: PurposeThe purpose of this paper is to review the current application areas of shape memory alloy (SMA) actuators in intelligent robotic systems and devices.Design/methodology/approachThis paper analyses how actuation and sensing functions of the SMA actuator have been exploited and incorporated in micro and macro robotic devices, developed for medical and non‐medical applications. The speed of response of SMA actuator mostly depends upon its shape and size, addition and removal of heat and the bias force appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
81
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 56 publications
0
81
0
1
Order By: Relevance
“…THE shape memory alloys (SMAs) have emerged as smart advanced materials in the recent past due to wide applications in bioengineering [1][2][3][4][5][6][7][8] , aerospace 1,[9][10][11] , robotics [12][13][14] , consumer products and industrial applications [15][16][17] , structures and composites 18 , automotive industry [19][20][21] , actuators and micro-electromechanical systems (MEMS) 1,2,[22][23][24] , and in fashion 25 . The SMAs are capable of memorizing their original shape.…”
mentioning
confidence: 99%
“…THE shape memory alloys (SMAs) have emerged as smart advanced materials in the recent past due to wide applications in bioengineering [1][2][3][4][5][6][7][8] , aerospace 1,[9][10][11] , robotics [12][13][14] , consumer products and industrial applications [15][16][17] , structures and composites 18 , automotive industry [19][20][21] , actuators and micro-electromechanical systems (MEMS) 1,2,[22][23][24] , and in fashion 25 . The SMAs are capable of memorizing their original shape.…”
mentioning
confidence: 99%
“…Evidently, quenching suppressed the ordering reaction, as in the case of α-(Au,Cu)→AuCu [23]. The α-(Cu,Au,Al)→Cu 3 Au transformation occurred about 20˚C higher than that of a binary (Au,Cu) alloy of the corresponding Au:Cu ratio, indicating that the addition of 15 at% Al raised the ordering temperature. This should be contrasted to the findings of Chapman and Gillam who reported that the addition of as little as 1.3 at.% Al to Cu 3 Au lowered the transformation temperature by 40˚C [24].…”
Section: α-Phasementioning
confidence: 94%
“…There is a small exothermic signal at ~320˚C in the DTA scan of Sample 6, cooled at 10˚C per second, evidently generated by the α-(Cu,Au,Al)→ Cu 3 Au ordering reaction. However, the strong characteristic superlattice {100} and {110} peaks for Cu 3 Al were absent in the XRD patterns which had been taken on samples annealed at 750˚C and then quenched. These samples showed only the peaks expected for α-(Au,Cu) plus some evidence for a small proportion of a second phase, possibly the β-phase.…”
Section: α-Phasementioning
confidence: 99%
See 1 more Smart Citation
“…[11] In microrobotics, [12] actuation may be achieved using materials that change shape upon stimulation. For example, shape-memory alloys (SMAs), [13] following mechanical deformation, recover their original shape when exposed to heat, and piezoelectric crystals expand (or contract) along specific axes when exposed to electric fields. [12,14] In macroscale machines/robots, shape-change actuation is demonstrated by the McKibben "air muscle," [15] which is driven pneumatically, and iRobot's "blob-bot," which operates by stiffening portions of an inflatable soft skin using jamming.…”
Section: Introductionmentioning
confidence: 99%